2017
DOI: 10.1177/0890334417692968
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity in Milk of Women With Mastitis: Potential Role of Coagulase-Negative Staphylococci, Viridans Group Streptococci, and Corynebacteria

Abstract: Many coagulase-negative staphylococci, viridans group streptococci, and corynebacteria, usually dismissed as contaminant bacteria, may play an important role as etiologic agents of mastitis. Proper diagnosis of mastitis should be established after performing microbiological testing of milk based on standardized procedures. A reliable analysis must identify the mastitis-causing pathogen(s) at the species level and its(their) concentration(s).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 51 publications
5
42
0
1
Order By: Relevance
“…Among the latter, S. epidermidis is emerging as the leading cause of mastitis worldwide (Contreras and Rodríguez, 2011). In this sense, the results of the present study confirm the important role that S. epidermidis plays as an etiologic agent in human mastitis, in agreement with previous studies (Delgado et al, 2008, 2009; Mediano et al, 2017). …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Among the latter, S. epidermidis is emerging as the leading cause of mastitis worldwide (Contreras and Rodríguez, 2011). In this sense, the results of the present study confirm the important role that S. epidermidis plays as an etiologic agent in human mastitis, in agreement with previous studies (Delgado et al, 2008, 2009; Mediano et al, 2017). …”
Section: Discussionsupporting
confidence: 93%
“…R. mucilaginosa , the most common species of this genus isolated in this study, has been previously involved in prosthetic device infections, which could be related, as in the case of coagulase-negative staphylococci, to the organism’s ability to produce a biofilm (Bruminhent et al, 2013). In this study, Corynebacterium and Rothia were found in 11 and 22% of samples, respectively, which suggests an important role in human mastitis pathogenesis, according to a previous study (Mediano et al, 2017). In relation to antimicrobial susceptibility, the VITEK 2 technology used for AST in this study is not available for these bacterial genera yet, and therefore the analyses of their antimicrobial resistance profiles will be part of a future study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Such diagnosis is made in virtually all cases by visual assessment of the breast, without supporting laboratory findings and ignoring that the evidence of a potential association Candida -painful breastfeeding is largely anecdotal [10,11]. Recently, studies applying milk microbial analysis (including some examining for the presence of yeasts) have shown that coagulase-negative staphylococci (CNS), streptococci (mitis and salivarius groups) and corynebacteria may be actually the agents responsible for such symptoms [1215]. However, studies directed to specifically and systematically investigate the presence or absence of Candida cells and/or DNA in a large collection of milk samples from women with these symptoms are very scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Los principales marcadores de inflamación son la plasmina y su zimógeno, el plasminóge-no, la elastasa y las catepsinas D y B, que provienen de leucocitos neutrófilos llegados desde la circulación 45 . También hay que considerar que las bacterias que causan la mastitis liberan en la leche sus propios enzimas que, además de causar proteólisis, dañan el tejido mamario y pueden enfermar al consumidor [46][47][48] . Teniendo en cuenta la calidad de las proteínas de la leche humana así como las identidades y actividades de sus enzimas y péptidos, el desarrollo y aplicación de metódicas de transcriptómica, proteómica y técnicas de bioinformática permitirán evaluar de mejor manera su funcionamiento y significado fisiológico.…”
Section: Hidrólisis De Las Proteínas De La Leche Materna Y Madurez Fetalunclassified